2016
DOI: 10.1111/cea.12765
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and asthma in Latino populations

Abstract: Background Younger maternal age at birth is associated with increased risk of asthma in offspring in European descent populations, but has not been studied in Latino populations. Objectives We sought to examine the relationship between maternal age at birth and prevalence of asthma in a nationwide study of Latino children. Methods We included 3473 Latino children aged 8–21 years (1696 subjects with physician-diagnosed asthma and 1777 healthy controls) from five U.S. centers and Puerto Rico recruited from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In a case-control study in the U.S., maternal age over 30 years at delivery was an independent predictor of food allergy in their children. 13 Several studies have shown associations between maternal age at delivery and risk of asthma in offspring; however, this relationship was inconsistent across different countries, [14][15][16][17] suggesting that there may be ethnic differences in the relationship between maternal age at delivery and development of allergic diseases in offspring. To date, the relationship between maternal age at delivery and the development of childhood allergic rhinitis has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study in the U.S., maternal age over 30 years at delivery was an independent predictor of food allergy in their children. 13 Several studies have shown associations between maternal age at delivery and risk of asthma in offspring; however, this relationship was inconsistent across different countries, [14][15][16][17] suggesting that there may be ethnic differences in the relationship between maternal age at delivery and development of allergic diseases in offspring. To date, the relationship between maternal age at delivery and the development of childhood allergic rhinitis has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] The role of maternal age at delivery in the development of asthma and allergy in the offspring is however uncertain: while some studies have shown that child birth at a young age is a risk factor for the development of asthma and allergy in the offspring, other studies have reported that old age at delivery is a risk factor, yet some studies found no relationship between mother's age at birth and offspring's asthma and allergy. [17][18][19] Although the specific mechanism through which maternal age at delivery influences the offspring's risk of developing asthma and allergy has not been elucidated, it has been suggested that this may involve a combination of hormonal, metabolic, immunological and genetic factors, which manifest during the fine-tuning of the processes of reproduction. 18 Clarifying the impact of maternal age at delivery on offspring's risk of developing asthma and allergy will contribute to ongoing evidence of the importance of reproductive events in later health of the child.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Informed by previous studies, age, 6 maternal age at birth, 42 sex, 43 socioeconomic status, 33,44 environmental exposures, [45][46][47][48][49] birth weight, 50,51 and global genetic ancestry 38,52 were considered potential confounders in the analyses. The socioeconomic indicators included were maternal educational attainment and insurance status.…”
Section: Covariate Selectionmentioning
confidence: 99%